Microstructure engineering by dispersing nano-spheroid cementite in ultrafine-grained ferrite and its implications on strength-ductility relationship in high carbon steel. (5th February 2018) - Prasad, C.; Bhuyan, P.; Kaithwas, C.; Saha, R.; Mandal, S.
Abstract: Thermo-mechanical processing is performed to engineer the microstructure comprising of nano-spheroidized cementites in ultrafine-grained ferrite in high carbon steel to enhance strength-ductility relationship. Spheroidization is achieved through heavy warm rolling (4-passes of 30% reduction at 823 K and 873 K) followed by extended annealing (1 h and 2 h) at the respective deformation temperatures. The influence of annealing temperature and time on the evolution of carbide precipitates, the extent of spheroidization and ferrite softening is investigated employing scanning electron microscopy, electron back scatter diffraction and transmission electron microscopy techniques. A near-complete spheroidization is achieved following heavy warm rolling and subsequent annealing for 2 h at 873 K (WR873K-2H). Although ferrite grain size increases with time and temperature of annealing, it ceases to cross the ultrafine regime (470–750 nm) due to the pinning effect of the carbides that restricts the migration of ferrite grain boundaries. A simultaneous increase in strength and ductility is achieved following heavy warm rolling and subsequent annealing for 1 to 2 h at 873 K. Maximum elongation (~ 30%) is achieved in the WR873-2H specimen in contrast to ~ 20% elongation in as-received specimen. Such an increase in ductility is due to the near-complete spheroidization as revealed by the ductile mode of fracture in fractrographic analysis. Graphical abstract: Highlights: Enhanced spheroidization of cementite in high-carbon steel is achieved through scheduled thermo-mechanical processing. Nano-dispersed cementites in ultrafine ferritesleadto the superior strength (825-876MPa) and ductility (25-30%). Coarser cementite spheroids formed at grain boundaries/triple junctions whereas the finer ones within the ferrite grains. Ferrite grains cease to cross the ultrafine regime (~ 470-750 nm) due to pinning effect of the cementites. Recovery is the dominant softening mechanism for ferrite as revealed from misorientation analysis.